Zakat on minerals: a theoretical analysis - Pg Mohd Faezul Fikri Ag Omar; Mohd Nur Hidayat Hasbollah Hajimin; Hazmi Dahlan (Journal of critical reviews, 2020)
Zakat is one of the obligations in Islam, as mentioned in the divine revelation. Apart from zakat imposed on an individual, zakat is also imposed on salary or income, business earnings, share or investment, agriculture produce, livestock, and gold and silver. Although technically both gold and silver are minerals, different categories of minerals are not given due attention regarding their zakat. This study analyses the zakat on minerals, which includes the discussion of its due obligation, the rate of zakat imposed and the haul and nisab on minerals, among others. The discussion on zakat on minerals in this study is based on the books written by prominent contemporary Muslim scholars. This study found that zakat on several minerals is yet to be exercised although it is obligatory to pay its due zakat. The lack of various mechanisms concerning the mineral assessment, evaluation methods to name it few, hindered the exercise of zakat on minerals to be implemented. This study sheds light on the need to introduce a comprehensive mechanism regarding zakat on minerals, thus expedite its implementation in Islamic countries. A clear new commitment on the zakat on minerals and its due attention should remain as the focus for future studies ahead.